2013
DOI: 10.1371/journal.ppat.1003470
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cell Permeability during Hantavirus Infection Involves Factor XII-Dependent Increased Activation of the Kallikrein-Kinin System

Abstract: Hemorrhagic fever with renal syndrome (HFRS) and hantavirus pulmonary syndrome (HPS) are diseases caused by hantavirus infections and are characterized by vascular leakage due to alterations of the endothelial barrier. Hantavirus-infected endothelial cells (EC) display no overt cytopathology; consequently, pathogenesis models have focused either on the influx of immune cells and release of cytokines or on increased degradation of the adherens junction protein, vascular endothelial (VE)-cadherin, due to hantavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
100
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(104 citation statements)
references
References 47 publications
2
100
0
2
Order By: Relevance
“…One study suggests that hantavirusinfected ECs transiently degraded VE-cadherin at a single specific time point (98). Consistent with our findings, another study of infected HUVECs demonstrated no change in VE-cadherin degradation in cells grown persistently in VEGF but didn't assess VEcadherin internalization or VEGF responsiveness (75). Interestingly, this paper demonstrates a role for kallikrein-directed bradykinin responses to increase the permeability of hantavirusinfected ECs (75).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…One study suggests that hantavirusinfected ECs transiently degraded VE-cadherin at a single specific time point (98). Consistent with our findings, another study of infected HUVECs demonstrated no change in VE-cadherin degradation in cells grown persistently in VEGF but didn't assess VEcadherin internalization or VEGF responsiveness (75). Interestingly, this paper demonstrates a role for kallikrein-directed bradykinin responses to increase the permeability of hantavirusinfected ECs (75).…”
Section: Discussionsupporting
confidence: 87%
“…HPS patients often seek medical attention as a result of the sudden onset of respiratory distress resulting from pulmonary edema that accumulates by as much as 1.0 liter per hour (2,(11)(12)(13). Potential pathogenic mechanisms accounting for the high rate of pulmonary fluid accumulation have yet to be demonstrated (13,18,22,41,47,48,(72)(73)(74)(75)(76) but appear be a consequence of the noncytolytic hantavirus infection of endothelial cells. Although, MECs and LECs are not permeabilized by hantavirus infection alone (47,(49)(50)(51)(52), hantavirus infection of the endothelium provides a means for the virus to alter EC responses that normally regulate capillary leakage and pulmonary fluid clearance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that FXII can be activated following local activation of endothelial cells. This is consistent with a previous study in which FXII was activated following Hantavirus-induced hypersensilisation of endothelial cells to VEGF [15]. In another in vitro study, the inflammatory cytokine BK stimulated cultured endothelial cells to secrete plasminogen, prostacyclin, thromboxane A 2 and NO, thereby regulating platelet function and promote fibrinolysis [16].…”
Section: +supporting
confidence: 91%